Hubungan TAM Factors dan Social Factors terhadap Attitude Towards Mobile App Use dan Intention to Purchase - Joice Livia Soedewa; Timotius Febry; Venny Soetedja (Universitas Ciputra Surabaya, 2021)
This Research was conducted to determine the relationship between costumers factors of Technology Acceptance Model (TAM factors) that represented by Perceived Usefulness PU and Perceived Ease of Use (PEOU) towards Attitude Towards Mobile App Use (ATMAU) in the daily lives of the people in Surabaya and Palu in using online marketplace. In the data collection process, researcher distributed questionnaires to 100 respondents who are used to shopping through shopee online marketplace. This research is conducted using the purposive sampling method. The results from T-statistic showed that the PU and PEOU variable has a significant effect on ATMAU because the number is greater than >1.96. The result on R-Square showed that PU and PEOU variable has a weak influence on ATMAU. The result of this study showed that PU and PEOU influence ATMAU partially, but simultaneously the effect is weak.